Penggunaan Aplikasi Tiktok terhadap Keterampilan Berbicara Mahasiswa - Dina Dahliana; Yumna; Nana Fauzana Azima; Nurhayati; Elis Ratna Wulan; Rahmia Tulljanah (Jurnal Elementaria Edukasia, 2024)
TikTok is an application that can post videos that are up to three minutes long. This application is in demand by various age levels. This research was conducted to understand how to use the TikTok application as a learning medium to develop one's speaking skills. In this study, the authors implemented qualitative research methods. The research data came from PGMI STAI Solok Nan Indah students, totaling 36 respondents. The data is obtained by angular spread online. To analyze, this study applies descriptive techniques. Theory triangulation is used in the validation technique in this study. The results of this study are the exposure of the use of the tiktok application to the speaking skills of students at STAI Solok Nan Indah. It is hoped that this innovation can make it easier for teachers or lecturers to improve students' speaking skills and make students as individuals who dare to convey ideas, as well as become generations of coherent, communicative, and easy-to-understand languages.